Effect of structural parameters on tensile properties of alumina fabrics. Issue 9 (May 2023) - Xie, Zhiyun; Li, Jiugang; Liu, Yang; Liu, Keshuai; Li, Wenbin
Alumina fabrics is a high temperature resistant textile material, and its mechanical tensile were studied in this work. The effect of fabric weaves, yarn linear densities and weft counts on the tensile breaking strength of alumina fabrics was analyzed. The results show that the tensile strength of fabric increases in the order of plain, twill, rearranged twill and satin weave. The number of interweaving points of the warp and weft yarns are the main reason for this difference. In addition, with the weft count as the invariant, when the weft count is small, the fabric strength gradually increases as the linear density of the yarn increases from 440 to 660 tex and then to 880 tex, but the growth rate gradually decreases. When the weft count increases to 7 number/1 cm, the fabric strength first increases and then decreases as the yarn linear density increased from 440 to 660 tex and then to 880 tex. When the yarn linear density is invariant, the fabric strength gradually decreases as the weft count increases from 5 to 6 to 7 number/1 cm, and the decrease rate increases gradually with the increase of the yarn linear density. The above results expose the relation between strength efficiency of warp yarn and the mechanical properties of the fabric. This study provides a theoretical basis for the weaving process of alumina fabrics.